Sorption of representative organic contaminants on microplastics: Effects of chemical physicochemical properties, particle size, and biofilm presence - Wenxuan Cui; Robert C. Hale; Yichao Huang; Fengli Zhou; Yan Wu; Xiaolin Liang; Yang Liu; Hongli Tan; Da Chen (Ecotoxicology and Environmental Safety, 2023)
Microplastic pollution has attracted mounting concerns worldwide. Microplastics may concentrate organic and metallic contaminants; thus, affecting their transport, fate and organismal exposure. To better understand organic contaminant-microplastic interactions, our study explored the sorption of selected polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), α-hexabromocyclododecane (α-HBCDD), and organophosphate flame retardants (OPFRs) on high-density polyethylene (HDPE) and polyvinylchloride (PVC) microplastics under saline conditions. Sorption isotherms determined varied between chemicals and between HDPE and PVC microplastics. Log Freundlich sorption coefficients (Log KF) for the targeted chemicals ranged from 2.01 to 5.27 L kg-1 for HDPE, but were significantly lower for PVC, i.e., ranging from Log KF data (2.84 – 8.58 L kg-1). Significant correlations between chemicals’ Log KF and Log Kow (octanol-water partition coefficient) indicate that chemical-dependent sorption was largely influenced by their hydrophobicity. Sorption was evaluated using three size classes (< 53, 53 – 300, and 300 – 1000 µm) of lab-fragmented microplastics. Particle size did not significantly affect sorption isotherms, but influenced the time to reach equilibrium and the predicted maximum sorption, likely related to microplastic surface areas. The presence of biofilms on HDPE particles significantly enhanced contaminant sorption capacity, indicating more complex sorption dynamics in the chemical-biofilm-microplastic system. Our findings offer new insights into the chemical-microplastic interactions in marine environment.